Technological Resources in the History Classroom - Fork, Rebecca (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
As a history teacher, it is not uncommon to hear students explain that they “hate” history class. Today, students are oftentimes turned off and uninterested when they are required to merely memorize dates, names, and events through traditional means like lectures. With the advances in technology and increasing presence of technological resources in school, teachers must seriously consider including technology resources in their toolbox of teacher methods. There are various types of technological resources available to the history teacher such as digital storytelling, online simulations, and virtual history museums. With these techniques incorporated into the classroom, teachers will grasp the interest of the students. The students intern will be able to increase their understanding and apply the lessons learned to become effective members of society.